Teaching exceptional children - Bayat, Mojdeh (New York : McGraw-Hill, 2012)
Teaching Exceptional Children presents theoretical information grounded in neuroscience and child development underpinning each disability along with specific behavioral characteristics of that disability. In addition, research-based methods of working with children related to each disability are important features of this book. Guidelines have also been presented to address sensory processing deficiencies manifested in regulatory disorders (such as ASD and ADHD) in young children.
Includes bibliographical references and index.
Keywords: Developmentally disabled children -- Education; Individualized instruction; Learning disabled children -- Education; Special education teachers -- Handbooks, manuals, etc